Treatment of Chronic Lymphocytic Leukemia in the Personalized Medicine Era - María Del Mar Sánchez Suárez; Alicia Martín Roldán; Carolina Alarcón-Payer; Miguel Ángel Rodríguez-Gil; Jaime Eduardo Poquet-Jornet; José Manuel Puerta Puerta; Alberto Jiménez Morales (MDPI AG, 2023)
Chronic lymphocytic leukemia is a lymphoproliferative disorder marked by the expansion of monoclonal, mature CD5+CD23+ B cells in peripheral blood, secondary lymphoid tissues, and bone marrow. The disease exhibits significant heterogeneity, with numerous somatic genetic alterations identified in the neoplastic clone, notably mutated TP53 and immunoglobulin heavy chain mutational statuses. Recent studies emphasize the pivotal roles of genetics and patient fragility in treatment decisions. This complexity underscores the need for a personalized approach, tailoring interventions to individual genetic profiles for heightened efficacy. The era of personalized treatment in CLL signifies a transformative shift, holding the potential for improved outcomes in the conquest of this intricate hematologic disorder. This review plays a role in elucidating the evolving CLL treatment landscape, encompassing all reported genetic factors. Through a comprehensive historical analysis, it provides insights into the evolution of CLL management. Beyond its retrospective nature, this review could be a valuable resource for clinicians, researchers, and stakeholders, offering a window into the latest advancements. In essence, it serves as a dynamic exploration of our current position and the promising prospects on the horizon.